2020
DOI: 10.2217/nnm-2019-0431
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antiproliferative Activity of Glioma-Derived Extracellular Vesicles

Abstract: Aim: To characterize a method to isolate glioma-derived extracellular vesicles (GEVs) and understand their role in immune system modulation and glioma progression. Materials & methods: GEVs were isolated by differential centrifugation from C6 cell supernatant and characterized by size and expression of CD9, HSP70, CD39 and CD73. The glioma model was performed by injecting C6 glioma cells into the right striatum of Wistar rats in the following groups: controls (C6 cells alone), coinjection (C6 cells + GEVs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Delivery of MSC-derived EVs to the CNS has been described in several studies [ 128 , 129 , 130 , 131 , 132 ]. In line with these findings, Scholl et al, [ 133 ] described the intranasal delivery of glioma-derived EVs obtained in vitro to glioma tissue in rats. The advantages of this administration route may be particularly important in the treatment of neurodegenerative disorders [ 134 ].…”
Section: Administration and Biodistributionmentioning
confidence: 80%
“…Delivery of MSC-derived EVs to the CNS has been described in several studies [ 128 , 129 , 130 , 131 , 132 ]. In line with these findings, Scholl et al, [ 133 ] described the intranasal delivery of glioma-derived EVs obtained in vitro to glioma tissue in rats. The advantages of this administration route may be particularly important in the treatment of neurodegenerative disorders [ 134 ].…”
Section: Administration and Biodistributionmentioning
confidence: 80%
“…The isolation was completed by centrifugation (100,000×g at 4 °C for 2 h). The supernatant was discarded, PBS was used to wash the pellet containing EVs, and the cell suspension was centrifuged at 100,000×g at 4 °C for 2 h [41]. Finally, the pellet was resuspended in 100 µL of PBS and stored at -20°C [38].…”
Section: Methodsmentioning
confidence: 99%
“…For example, in 2020 the research group led by Fabrício Figueiró demonstrated that glioma-derived extracellular vesicles expressing CD9, HSP70, CD39, and CD73, and producing adenosine, reduced glioma progression by modulating the tumor microenvironment. Thereby, a reduction in tumor size occurred by acting on cell proliferation [85].…”
Section: Adenosine (Ado) In the Tme: Potent Mediator Of Immunosuppressionmentioning
confidence: 99%